Analisis Strategi Peningkatan Sertifikasi Halal Ultra Mikro Di Tanjung Selor Kalimantan Utara - Arifin, Zainul; Aini, Nur (Jurnal Ilmiah Ekonomi Islam, 2025)
This research aims to analyze the strategies implemented to enhance halal certification for Ultra Micro businesses in Tanjung Selor, North Kalimantan, and to identify the internal and external factors influencing these strategies based on SWOT analysis. This is a qualitative study utilizing in-depth interview techniques for data collection. Data sources include the local Religious Affairs Office of North Kalimantan (Kanwil Kemenag Kalimantan Utara), PPH Tanjung Selor, and certified Ultra Micro business actors. The data analysis technique used in this study is SWOT analysis, focusing on internal and external factors of the strategy for enhancing halal certification for SMEs in Tanjung Selor. The results indicate that the strategy for enhancing halal certification for Ultra Micro businesses in Tanjung Selor involves three main steps: regular socialization, technical guidance, and direct assistance. External aspects show that halal certification increases product trust and market appeal. Internal factors in the SWOT analysis include the ease of self-declare procedures and proactive assistance, while external factors include the potential for further guidance and free self-declare programs. However, weaknesses such as lack of initial socialization and IT comprehension among SMEs, as well as threats like lack of interest and awareness from SMEs, were identified.